2010
DOI: 10.1158/1541-7786.mcr-09-0358
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Protein Kinase C ζ Exhibits a Proapoptotic Function in Ovarian Cancer

Abstract: Intracellular signaling governed by serine/threonine kinases comprises the molecular interface between cell surface receptors and the nuclear transcriptional machinery. The protein kinase C (PKC) family members are involved in the control of many signaling processes directing cell proliferation, motility, and survival. Here, we examined a role of different PKC isoenzymes in protein phosphatase 2A (PP2A) and HRSL3 tumor suppressordependent cell death induction in the ovarian carcinoma cell line OVCAR-3. Phospho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 71 publications
(73 reference statements)
2
24
0
Order By: Relevance
“…These results are in agreement with previous reports showing that caspase activation and apoptosis promoted by activated G␣q is not blocked by inhibitors of IP 3 -or PKC-dependent signaling (38). Also, the role of PKC as a pro-apoptotic protein appears to have a crucial effect on the repression of tumorigenesis in ovarian (39) and prostate cancer (40). Interestingly, pharmacological blockade of ERK5 partly inhibited cell death promotion downstream of the Gq/PKC axis.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previous reports showing that caspase activation and apoptosis promoted by activated G␣q is not blocked by inhibitors of IP 3 -or PKC-dependent signaling (38). Also, the role of PKC as a pro-apoptotic protein appears to have a crucial effect on the repression of tumorigenesis in ovarian (39) and prostate cancer (40). Interestingly, pharmacological blockade of ERK5 partly inhibited cell death promotion downstream of the Gq/PKC axis.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, PKC in ovarian cancer cells can act as a negative regulator of cell survival via regulation of the proapoptotic functions of protein phosphatase 2A (a survival phosphatase) and HRSL3 (a class II tumor suppressor family; also known as H-REV107-1) [394].…”
Section: Ovarianmentioning
confidence: 99%
“…Contentious opinions have been expressed in the past about the pro-or anti-apoptotic roles played by PKCζ (39)(40)(41). Our results from proteomics analysis clearly demonstrated that PKCζ changed nearly 86% of its interacting proteins at the NMs of C4-I cells.…”
Section: Discussionmentioning
confidence: 65%